FAKTOR-FAKTOR YANG MEMENGARUHI DIVIDEND POLICY DENGAN PROFITABILTIY SEBAGAI VARIABEL MODERASI - Angelia, Angelia; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this research is to find empirical evidence regarding the effect of leverage, liquidity, and institutional ownership on dividend policy with profitability as moderating variable. Purposive sampling method used in this research to find the total of 54 samples of consumer cyclical and non-cyclical companies registered in Indonesia Stock Exchange from 2019-2021. Data processing techniques used in this research are multiple regression analysis and moderatated regression analysis with the help of EViews 10 application. The results obtained through the data processing that leverage has positive and significant effect on dividend policy. While, liquidity, institutional ownership, and profitability have negative and insignificant effects on dividend policy. Profitability cannot moderate the effect of leverage and liquidity on dividend policy. On the other hand, profitability can moderate by strengthening the effect of institutional ownership on dividend policy. The implication of this study is the need to increase company’s leverage so that the company will give positive signal to the shareholders by paying higher amounts of dividends.